Towards Settler Responsibility in Conservation - Stein, Sharon; Ahenakew, Cash; Oliveira da Silva Huni Kui, Shyrlene; Bowness, Evan; Mendes, Wilson; Evans, Steve (ACME, 2023)
This conceptual paper reviews recent efforts to confront colonialism in conservation, with an emphasis on the challenges and complexities that have emerged among settler organizations engaged in this work. We consider recent academic and grey literature in the field in order to map different approaches to conservation, including the emerging interface of Indigenous and western approaches. We also map different approaches to Indigenous engagement undertaken by settler conservation organizations, including representation, recognition, redistribution, and reparation. We suggest that regardless of their approach, in order to create the conditions for truly reciprocal collaborations with Indigenous Nations, settler conservation organizations would need to accept their responsibilities to interrupt and redress western conservation’s colonial foundations, support Indigenous sovereignty, rights, and resurgence (including by supporting Indigenous approaches to conservation), and commit to the difficult, long-haul work of reorienting their approach to relationships away from patterns of paternalism and extraction toward trust, respect, reciprocity, consent, and accountability.